2022
DOI: 10.1111/jse.12817
|View full text |Cite
|
Sign up to set email alerts
|

Linked selection, ancient polymorphism, and ecological adaptation shape the genomic landscape of divergence in Quercus dentata

Abstract: Multiple evolutionary forces contribute to heterogeneous genomic landscapes; however, disentangling their relative contributions is challenging. We sampled nine populations across the distribution of Quercus dentata, a dominant forest tree in East Asia, and used whole-genome sequencing data to investigate mechanisms underlying divergence. We identified two genetic groups (north and south) that diverged ~1.84 million years ago, consistent with the uplift of the Qinling Mountains during the Pleistocene. The nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 101 publications
(156 reference statements)
1
5
0
Order By: Relevance
“…Within our B. platyphylla samples, we found three genetic clusters with some admixed individuals between them. The three clusters seem to mirror similar phylogeographic breaks in many other plant species (Bai et al, 2016; Fan et al, 2013; Ye et al, 2017; Zhou et al, 2022) and our interpretation of B. platyphylla population structure is similar to that of Chen and Lou (2019). Our fastsimcoal results suggest that the three B. platyphylla populations exchanged genetic material soon after their divergence and recently but endured a long period of isolation in between these contacts (Figure 3d).…”
Section: Discussionsupporting
confidence: 84%
“…Within our B. platyphylla samples, we found three genetic clusters with some admixed individuals between them. The three clusters seem to mirror similar phylogeographic breaks in many other plant species (Bai et al, 2016; Fan et al, 2013; Ye et al, 2017; Zhou et al, 2022) and our interpretation of B. platyphylla population structure is similar to that of Chen and Lou (2019). Our fastsimcoal results suggest that the three B. platyphylla populations exchanged genetic material soon after their divergence and recently but endured a long period of isolation in between these contacts (Figure 3d).…”
Section: Discussionsupporting
confidence: 84%
“…These results indicate a pattern of IBE generated by adaptation to local environments (Wang & Bradburd, 2014). The pervasive signatures of local adaptation and their influences on the spatial distribution of genetic variation have been well documented in forest trees (Lind et al, 2018; Savolainen et al, 2007; Xia et al, 2018; Zhao et al, 2020; Zhou, Shi, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In total, 55 natural populations (135 individuals) were sampled, covering the main distribution of the four oak species in China, including 18 populations (34 individuals) of Quercus acutissima , 24 populations (47 individuals) of Quercus variabilis , nine populations (38 individuals) of Quercus dentata , and four populations (16 individuals) of Quercus griffithii (Table ). Whole‐genome sequencing data for these samples were obtained from previous publications (Liang et al, 2022; Zhou et al, 2022a), with the exception of eight Q. griffithii individuals sequenced in this study. For these new samples, young leaves were collected from each individual and immediately dried in silica gel for DNA isolation.…”
Section: Methodsmentioning
confidence: 99%
“…Interspecific hybridization is prevalent within sections of Quercus and less common between sections and subgenera (Crowl et al, 2020; Hipp et al, 2020; Li et al, 2021; Fu et al, 2022; Zhou et al, 2022b). Previous studies have suggested that linked selection has played a major role in shaping the heterogeneous genomic landscape of oak species (Gao et al, 2021; Liang et al, 2022; Zhou et al, 2022a). Here, we use comparative population genomics approaches to understand the relative contributions of different types of linked selection to the formation of shared and lineage‐specific islands.…”
Section: Introductionmentioning
confidence: 99%